An Intratracheal Instillation Bioassay System for Detection of Lung Toxicity Due to Fine Particles in F344 Rats - Yokohira, Masanao (The Japanese Society of Toxicologic Pathology, 2009)
It is an urgent priority to establish in vivo bioassays for detection of hazards related to fine particles, which can be inhaled into deep lung tissue by humans. In order to establish an appropriate bioassay for detection of lung damage after particle inhalation, several experiments were performed in rats using quartz as a typical lung toxic particle. The results of pilot experiments suggest that Days 1 and 28 after intratracheal instillation of 2 mg of fine test particles in vehicle are most appropriate for detection of acute and subacute inflammatory changes, respectively. Furthermore, the BrdU incorporation on Day 1 and the iNOS level on Day 28 proved to be suitable end-point markers for this purpose. An examination of the toxicity of a series of particles was performed with the developed bioassay. Although some materials, including nanoparticles, demonstrated toxicity that was too strong for sensitive assessment, a ranking order could be clarified. The bioassay thus appears suitable for rapid hazard identification with a possible ranking of the toxicity of various particles at single concentrations.